(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Conventional surgical techniques have relied on 2D medical imaging for surgical planning and correction of a limb deformity. This result in certain deviations observed post-surgery from the conventional average values of limb and joint angles. Computer Aided Design (CAD) and manufacturing technology, especially additive manufacturing, provide a solution through patient specific surgical guides. Patient specific surgical guides enable accurate cut of the bone and anatomically accurate corrections, mitigating the drawbacks of conventional surgery planning. This paper discusses the technology, materials, surgical planning technique and corroborates the accuracy of correction achieved with respect to the pre-operative planning.